El Fenómeno "Lambada": Globalización e Identidad - Leonardo García (Centre de Recherches sur les Mondes Américains, 2008)
This paper analyses the “Lambada” musical hit inside the globalization context of the end of the 20th century, by treating its expansion through the socio-political changes and the post-modernism of the nineties. In fact, besides being a commercial “summer hit”, “Lambada” can also be associated to the claim of the minorities as well as to the development of a serial music industry. We will analyze the genre lambada from its Brazilian origins to its global commercial success, by evocating the marginality of some handcrafted productions as well as its integration into the genesis of a new global Latin-American imaginary. May “Lambada” be, besides the musical success, a messianic symbol of the end of the Cold War and the millenary?